2017
DOI: 10.1080/13880209.2017.1345950
|View full text |Cite
|
Sign up to set email alerts
|

Quillaja saponaria bark saponin protects Wistar rats against ferrous sulphate-induced oxidative and inflammatory liver damage

Abstract: Context: Saponins from different sources are historically reported in Chinese medicine to possess many beneficial effects. However, insufficient experimental data are available regarding the hepatoprotective potential of Quillaja bark saponin.Objective: The protective effect of Quillaja saponaria Molina (Quillajaceae) bark triterpenoid saponin against iron-induced hepatotoxicity is compared to the standard N-acetylcysteine in adult male Wistar rats.Materials and methods: Animals were divided into (six) groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Thought-provokingly, Abdel-Reheim et al [59] demonstrated that bark saponins from Q. saponaria are interesting hepatoprotective agents. In this study, the authors verified that saponin significantly decreased the elevation of ALT (achieving 57% hepatotoxicity control), AST (66%), ALP (76%), GGT (60%), NOx (77%), TC (70%), MDA (65%), LDH (54%), TG (54%), and total (54%), direct (54%), and indirect (54%) bilirubin, coupled with increased GSH (219%) and albumin (159%) levels.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thought-provokingly, Abdel-Reheim et al [59] demonstrated that bark saponins from Q. saponaria are interesting hepatoprotective agents. In this study, the authors verified that saponin significantly decreased the elevation of ALT (achieving 57% hepatotoxicity control), AST (66%), ALP (76%), GGT (60%), NOx (77%), TC (70%), MDA (65%), LDH (54%), TG (54%), and total (54%), direct (54%), and indirect (54%) bilirubin, coupled with increased GSH (219%) and albumin (159%) levels.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The decrease in TG and TC serum levels can be explained by the decrease in intestinal cholesterol absorption and by the reduction in cholesterol levels, accompanied by an increase in the HMG-CoA reductase activity and LDL receptor levels in the liver [62]. In addition, the immunohistochemical results help to explain Quillaja bark saponins’ protective activity, since saponins suppressed NOS expression, attenuating oxidative and nitrosative stress [59].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The total saponin content of the plant extract can exceed 100 members, most of which are Quil‐A (Barr et al, 1998). Quillaja bark saponin is characteristically distinct in chemical composition from other triterpenoid plant saponins (Ahmed Abdel‐Reheim et al, 2017). The distinction can be expressed by the domain of fatty acids and triterpene aldehydes in carbon 4 triterpene (Kensil et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The bark of the plant also exhibited antitumor, hepatoprotective, antiviral, antibacterial, and antiparasitic potential ( 151 ). As hepatoprotective agent, bark saponin decreased the iron-induced elevation of ALT, AST, ALP, GGT, LDH, MDA, NOx, TC, and TG, as well as the total direct and indirect bilirubin and albumin levels ( 152 ).…”
Section: Medicinal Plants Exhibiting Immunomodulation Activitymentioning
confidence: 99%